Criminalizing Adultery in Unregistered Marriages: A Case Study of Sukabumi District Court Decision No. 51/Pid.B/PN.Skb from Islamic and Indonesian Legal Perspectives - Yayan Mulyana; Munandi Shaleh; Juhdi Rifa’i; Diana Farid (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
Unregistered marriage (nikah siri) remains a persistent legal phenomenon in Indonesia, generating ongoing debates regarding the relationship between religious validity and state legal recognition. The issue becomes more complex when an unregistered marriage is conducted by an individual who remains legally married under state law, as illustrated by Sukabumi District Court Decision No. 51/Pid.B/2023/PN.Skb, which imposed criminal sanctions for adultery. This study aims to examine the court's legal reasoning and evaluate its consistency with the principles of Islamic law and Indonesian positive law. The research employs a normative legal method using statutory, conceptual, and case approaches by analyzing legislation, legal doctrines, and judicial decisions. The findings reveal a fundamental divergence between Islamic law and Indonesian positive law regarding the legal validity of marriage. Under Islamic law, a marriage that fulfills the essential legal requirements remains valid despite the absence of state registration; therefore, the marital relationship cannot automatically be classified as adultery. In contrast, Indonesian positive law treats marriage registration as a crucial element for establishing legal status, allowing the absence of official registration to influence the assessment of criminal liability. The analyzed judgment demonstrates that the court prioritized formal legal evidence and administrative legality over the religious validity of the marriage. These findings highlight the need to harmonize criminal law, marriage law, and Islamic law to strengthen legal certainty while ensuring substantive justice in adjudicating cases involving unregistered marriages.